Spotlight on iron and ferroptosis: research progress in diabetic retinopathy - Ouyang, Junlin; Zhou, Ling; Wang, Qing (Frontiers in Endocrinology, 2023)
Iron, as the most abundant metallic element within the human organism, is an indispensable ion for sustaining life and assumes a pivotal role in governing glucose and lipid metabolism, along with orchestrating inflammatory responses. The presence of diabetes mellitus (DM) can induce aberrant iron accumulation within the corporeal system. Consequentially, iron overload precipitates a sequence of consequential adversities, subsequently setting in motion a domino effect wherein ferroptosis emerges as the utmost pernicious outcome. Ferroptosis, an emerging variant of non-apoptotic regulated cell death, operates independently of caspases and GSDMD. It distinguishes itself from alternative forms of controlled cell death through distinctive morphological and biochemical attributes. Its principal hallmark resides in the pathological accrual of intracellular iron and the concomitant generation of iron-driven lipid peroxides. Diabetic retinopathy(DR), established as the predominant cause of adult blindness, wields profound influence over the well-being and psychosocial strain experienced by afflicted individuals. Presently, an abundance of research endeavors has ascertained the pervasive engagement of iron and ferroptosis in the microangiopathy inherent to DR. Evidently, judicious management of iron overload and ferroptosis in the early stages of DR bears the potential to considerably decelerate disease progression. Within this discourse, we undertake a comprehensive exploration of the regulatory mechanisms governing iron homeostasis and ferroptosis. Furthermore, we expound upon the subsequent detriments induced by their dysregulation. Concurrently, we elucidate the intricate interplay linking iron overload, ferroptosis, and DR. Delving deeper, we engage in a comprehensive deliberation regarding strategies to modulate their influence, thereby effecting prospective interventions in the trajectory of DR's advancement or employing them as therapeutic modalities.